Potential impact of COVID-19 on Indian population, confirmed, deceased and recuperations from novel coronavirus: a current evidence-based review - Ravi, Ravi Chandra; Ponugubati, Charishma Chowdary (International Journal Of Community Medicine And Public Health, 2020)
In the ending of 2019 China has shattered the world by bring up news of pneumonia of unfamiliar aetiology in Wuhan, Hubei. The amount of cases with similar presentation began to strike high. It was formerly addressed as 2019 novel coronavirus (2019-nCoV) and currently called as severe acute respiratory syndrome coronavirus 2 (SARSCoV-2). The virus has affected 209 countries globally and was declared to be a pandemic issue by WHO. India was no less. Cases in India increased at an exponential rate. In order to curb this the Indian government halted the intercountry travel. This review enlightens the potential impact of COVID-19 on the Indians and people capitulated by the virus and fought back successfully.